The valuation impact of reconciling pro forma earnings to GAAP earnings - Zhang, Huai (2013)
Regulation G requires all companies to quantitatively reconcile pro forma earnings with GAAP earnings. This paper provides three findings related to the impact of reconciliations on mispricing of pro forma earnings. First, prior to Reg G, we find that mispricing of pro forma earnings is limited to firms with low reconciliation quality. There is no evidence of mispricing for firms with high reconciliation quality. Second, we find no evidence of mispricing after Reg G. Third, there is a cross-Reg G reduction of mispricing for firms whose reconciliation quality improves, and there continues to be no mispricing for firms that have high reconciliation quality both before and after Reg G. Together, our results support the notion that better reconciliations reduce the extent of mispricing.